2022
DOI: 10.1097/gme.0000000000002020
|View full text |Cite
|
Sign up to set email alerts
|

Potential effects of virtual interventions for menopause management: a systematic review

Abstract: Importance: Menopausal women are one of the fastest growing demographic groups globally. Virtual interventions have emerged as alternate avenues for menopausal women to manage and cope with their symptoms.Objective: The purpose of this review is to summarize existing research on the potential effects of virtual interventions for menopause management.Evidence Review: This systematic review was written in accordance with Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. MEDLINE, Psyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…Another study in Iran confirmed the effect of virtual programs on improving the quality of life, vasomotor symptoms, and physical and sexual aspects of women [ 26 ]. Although Eun-Ok et al (2017) [ 27 ] believe that these effects may be influenced by the Hawthorn effect, other studies that reported the improving effect of mHeath and virtual programs on objective outcomes, such as waist circumference, weight, blood pressure, serum lipid levels and pain [ 25 , 28 ], indicate that the effect of mHeath on health-related outcomes is more real than can be justified by the Hawthorn phenomenon.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Another study in Iran confirmed the effect of virtual programs on improving the quality of life, vasomotor symptoms, and physical and sexual aspects of women [ 26 ]. Although Eun-Ok et al (2017) [ 27 ] believe that these effects may be influenced by the Hawthorn effect, other studies that reported the improving effect of mHeath and virtual programs on objective outcomes, such as waist circumference, weight, blood pressure, serum lipid levels and pain [ 25 , 28 ], indicate that the effect of mHeath on health-related outcomes is more real than can be justified by the Hawthorn phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the study by Kashfi et al (2021) [ 26 ] showed that an educational program on the WhatsApp platform improved the quality of life of postmenopausal women. However, a review study reported that the results of studies on the effect of virtual programs on sexual performance were contradictory [ 25 ]. Therefore, it is suggested that studies with a large sample size be repeated so that the impact of mhealth interventions on sexual performance and the quality of marital relationships can be assessed with more certainty.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Data synthesis of the intervention characteristics will be conducted using descriptive synthesis by summarising and tabulating the data and presenting them according to the research questions. Virtual care will be categorised by virtual care modalities: telephone, videoconferencing, store and forward, remote monitoring, websites and apps,24 and further differentiated into purely synchronous interactions, purely asynchronous, or combined synchronous and asynchronous interactions,1 and hybrid and standalone interventions 25. Synchronous delivery facilitates remote real-time feedback with both audio and visual cues available.…”
Section: Methods and Analysismentioning
confidence: 99%